2011
DOI: 10.1186/1475-2891-10-134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal food and micronutrient supplementation on child growth from birth to 54 months of age: a randomized trial in Bangladesh

Abstract: BackgroundThere is a lack of information on the optimal timing of food supplementation to malnourished pregnant women and possible combined effects of food and multiple micronutrient supplementations (MMS) on their offspring's growth. We evaluated the effects of prenatal food and micronutrient interventions on postnatal child growth. The hypothesis was that prenatal MMS and early invitation to food supplementation would increase physical growth in the offspring during 0-54 months and a combination of these int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
1
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(103 citation statements)
references
References 31 publications
(35 reference statements)
5
90
1
7
Order By: Relevance
“…In Bangladesh, food rations combined with micronutrients tablets given in early gestation resulted in a reduced proportion of stunting from early infancy up to 54 months for boys and a higher infant mortality. 14 We previously reported that providing pregnant women with lipid-based nutrient supplementation (LNS) increased birth length by 4.6 mm (P = .001) and weight by 31 g (P = .197). 15 In the current study, we assessed the effect of prenatal LNS compared with MMNs on postnatal growth and nutritional status during the first year of life.…”
mentioning
confidence: 98%
“…In Bangladesh, food rations combined with micronutrients tablets given in early gestation resulted in a reduced proportion of stunting from early infancy up to 54 months for boys and a higher infant mortality. 14 We previously reported that providing pregnant women with lipid-based nutrient supplementation (LNS) increased birth length by 4.6 mm (P = .001) and weight by 31 g (P = .197). 15 In the current study, we assessed the effect of prenatal LNS compared with MMNs on postnatal growth and nutritional status during the first year of life.…”
mentioning
confidence: 98%
“…Nevertheless, we have identified studies, both from Guatemala and in the international literature, with which to compare the present findings. Birth length is often part of protocols in long-term cohort studies bridging from birth through childhood and towards adulthood (40)(41)(42)(43)(44)(45) or short-term, longitudinal observational studies seeking to find correlates of early growth or health (46)(47)(48)(49)(50)(51)(52)(53) . More recently, length is measured at birth as part of studies evaluating inter-pregnancy interventions in (4) .…”
Section: Discussionmentioning
confidence: 99%
“…Early nutrition-specific interventions like prenatal multiple micronutrient supplements reduce the risk of SGA and LBW babies [32] and reduce postnatal stunting [14, 32, 33]. Interventions that focused on multiple micronutrients along with balanced energy and protein during pregnancy have even greater results on SGA [14, 32, 34].…”
Section: Linear Growth From Preconception To Beyond the First 1000 Dmentioning
confidence: 99%